(untitled) (Revista de Crítica Literaria Latinoamericana, 2018)
Hispanic Philippine Modernism has not been analyzed so far in any work that studies, globally, its nature and development in the framework of the Fin de Siècle’s critical and poetic context. For that reason, its canon remains being evaluated by the hermeneutic tradition that started from the antimodernist premises of the time. This work intends to review the Golden Age of Hispanic Philippine letters from the assumptions of Comparativism. Taking into account both the poetic texts and the critical paratexts, I question the patriotic and Hispanicizing paradigm because of its dialogic relationships with the literary system of the former mother country and with Latin American Modernism.